Dataset from: “Frequencies of β-casein variants and their influence on genetic merit for production traits in Holstein cows [Conjunto de datos] - Caffaro, María Eugenia; Raschia, Maria Agustina; Maizon, Daniel Omar; Poli, Mario Andres (2024)
This study was supported by Instituto Nacional de Tecnología Agropecuaria (grants PD I108, PD I087, PD I112); ANPCyT (PICT-2017-4208); and FAO-IAEA (CRP D3.10.30).